Web-based-Research as Critical Pedagogy: A Reflection on its Application to Undergraduate Management Education. - Coronado, Gabriela (Journal of University Teaching and Learning Practice, 2011)
In disciplines such as Management, where research capacity is not seen as an obvious workplace skill, it is difficult to get students to engage in research activities. They see them as too difficult and without value. However, research activities in undergraduate Management education are vital as tools for developing key learning attributes such as critical thinking and skills in analysis and argument. Convinced of the high value of integrating research activities into undergraduate Management Education, I took on the challenge to find alternative ways for students to develop their research capacity and engage in actual research. Drawing on reflections on my experience of teaching undergraduate management subjects with research components, in this paper I discuss how Web-based research can promote critical thinking and raise consciousness among management students. This experience included designing strategies to introduce a form of electronic literacy into undergraduate education, to assist students to learn how to use the Web critically for research purposes, while enhancing learning based on conventional resources. In the methodology I propose for researching contemporary issues by collecting and analysing data from the Web I adapt the critical pedagogy of Freire for adult literacy into new forms of literacy involving critical use of the new media of communication.